Intellectual Capital: its Identity and Role in the Knowledge Economy - БлиновСтанислав Сергеевич (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2011)
Today, intellectual capital is one of the important directions in financial management. The article displays the degree of importance of this resource, both at the state level and at company level. Theoretical and methodological aspects of intellectual capital concerning the wording of its definition and critical analysis of the strengths and weaknesses of models for assessing intellectual capital are presented in this paper. The basic characteristics of the intellectual capital and its distinctive features in comparison with monetary-material resources are allocated. It is concluded that implementation of these propositions in the aggregate, may contribute to the goal of creating new levers of company value.